Lessons learned: Linking patient-reported outcomes data with administrative databases - Laura Davis; Alyson Mahar; Lev Bubis; Qing Li; Haoyu Zhao; Lesley Moody; Rinku Sutradhar; Lisa Barbera; Natalie Coburn (International Journal of Population Data Science, 2018)
Introduction Since 2007, Cancer Care Ontario (CCO) has systematically collected patient-reported outcomes (PROs) in the form of symptom data, for cancer outpatients visiting regional cancer centres or affiliate institutions. Data are used in real-time to facilitate conversation between clinicians and patients and have recently been combined with provincial administrative databases.